PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ENGGAL LARAS LANGGENG DI PEKANBARU - Dehotman, Khornelis (Eko dan Bisnis: Riau Economic and Business Review, 2020)
This research was conducted at PT. Enggal Laras Langgeng In Pekanbaru, to find out effect of work environment on employee performance in PT. Enggal Laras Langgeng in Pekanbaru. Sampling using the saturated sample method that is as many as 35 respondents. The method of collecting data uses two methods, questionnaires and observation. The data analysis technique used is simple linear regression. Data processing is done with SPSS version 24 windows. Form the processing od the data performed, a simple linear regression equation is obtained, namely Y= 1,810 + 0,797X. The t test (partial) shows that work environment where the results show that t hitung (13,790) is greater than t indicated (2,034), with a significance level of 0,000 less than 0.05. This is also indicated by the coefficient of determination (ð‘…2) it is known that working disipline has an effect of 0,852 on employee performance in PT. Enggal Laras Langgeng in Pekanbaru. Therefore effect of work environment on employee performance in PT. Enggal Laras Langgeng in Pekanbaru is 85,2%, while the remaining 14,8% influenced by other factors not examined by the researcher